2017
DOI: 10.1007/s00701-017-3213-1
|View full text |Cite
|
Sign up to set email alerts
|

5-ALA fluorescence in intraparenchymal endodermal cysts

Abstract: In recent years, new indications have been suggested for 5-ALA, particularly for cystic lesions. We report the use of 5-ALA fluorescence in an intraparenchymal supratentorial endodermal cyst of a 52-year-old female presenting with headache, progressive right side hemiparesis and anomic aphasia. She underwent an image-guided 5-ALA-assisted left minicraniotomy for fenestration of the cystic lesion into the ventricular system. The capsule of the cyst was noted to fluoresce with 5-ALA. She recovered from the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As far as the authors are aware, this is the first report of a 5-ALA fluorescent PGNT. Our group has reported other cases as well, of benign lesions that were fluorescent with 5-ALA [10]. Other cases of non-diffuse gliomas have been reported as well as potential target for 5-ALA-assisted resection, for example pilomyxoid [3] and pilocytic astrocytomas [5].…”
Section: Discussionmentioning
confidence: 70%
“…As far as the authors are aware, this is the first report of a 5-ALA fluorescent PGNT. Our group has reported other cases as well, of benign lesions that were fluorescent with 5-ALA [10]. Other cases of non-diffuse gliomas have been reported as well as potential target for 5-ALA-assisted resection, for example pilomyxoid [3] and pilocytic astrocytomas [5].…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, Labrador et al reported intraoperative fluorescence in other cases of benign brain tumors. 11 Based on these reports, it should be noted that photodynamic testing is not specific to malignant brain tumors. Regarding the latter finding, if PGNT had been predicted from the preoperative imaging findings mentioned above, an accurate rapid intraoperative diagnosis could have been achieved by using multiple pathological specimens, focusing on the presence of biphasic cell patterns composed of glial and nerve cells.…”
Section: Discussionmentioning
confidence: 99%